Video-based health education to support insulin therapy in diabetes mellitus patients - Dinda M.N. Ratri; Khusnul Fitri Hamidah; Arina D. Puspitasari; Muhammad Farid (SAGE Publishing, 2020)
Background: The improper use of insulin usually leads to some unexpected effects, hence, there is a need for right usage. Lack of knowledge and of understanding are key factors leading to the occurrence of medication errors, which could be avoided with proper education. Therefore, an appealing education alternative, such as video, is needed to improve patient's knowledge and attitudes towards insulin therapy. Design and Methods: One-group pretest and posttest design were conducted on 100 patients with type 2 diabetes mellitus who were receiving subcutaneous insulin therapy at Internal Medicine Unit in Universitas Airlangga Teaching Hospital. The patients filled the provided questionnaires to measure their knowledge and attitudes, before and after watching the video on insulin therapy education. Then, data obtained were analysed with SPSS using Wilcoxon Signed Rank Test Method. Results: Based on the results, there was an increase in the value of the patient's knowledge, with the value of Z=-8.212 and P<0.05. Similarly, there was an increase in the patient's attitudes with the value of Z=-8.234 and P<0.05. Conclusions: Insuline therapy video increases the knowledge and improves the attitude of diabetes mellitus patients towards insulin therapy.